Pigskin Treatment Using Different Food-Grade-Acids: Effects on The Physicochemical Characteristics of The By-Products - Velazquez, Diego Ezequiel; Sánchez, Mariana Marta; Latorre, Maria Emilia (University of Sultan Ageng Tirtayasa, 2023)
Upcycling foods contribute to reducing food loss and waste and provide sustainable solutions to novel products. In the present work, it was studied the use of food-grade acids (Acetic(AH), Latic(AL), Citric(AC), and Ascorbic(AA) acid) to obtain pigskin by-products, acid soluble collagen (ASC) and gelatin (G). The aim was to evaluate the effect of the use of different food-grade-acids on pigskin by-products characteristics. The physicochemical and thermal characteristics, including Hydroxiproline (Hyp), pH, Differential Scanning Calorimetry (DSC), and color were evaluated on by-products. The ASC and G solutions pH´s showed relation with the acid solution pH used. The AH and AA ASC fractions, showed lower Hyp content than AC and AL-treatments. By contrast, G Hyp-content was higher for AH and AA than AC and AL-treatments. The dried ASC-AH and -AA thermal transition temperatures (Td) resulted lower than AL and AC Td. The four dried-G samples showed an endothermic signal around 120 °C but with differences on enthalpy values. Current results suggest that the acid used and the pH of the solution during the thermal process would affect the physical-chemical properties of the by-products. The possibility to obtain different pigskin by-products using food grade acid could be an option for obtaining novel ASC and G use. Independently of the treatment, the G by-product was the main yield. Likewise, further studies are required to understand the by-products chemical differences and their potential uses.